Photon‐to‐photon polarization modulation using Mxene thin film as modulator. Issue 9 (5th March 2022) - Tiu, Z. C.; Tan, S. J.; Samion, M. Z.; Yusoff, N.; Ahmad, H.; Harun, S. W.
Abstract: In this work, photon‐to‐photon polarization modulation is experimentally demonstrated using a Mxene material, Ti2C thin film as a modulator. S‐band signal (1500 nm) polarization state is modulated by a control pump (1400 nm) in the Ti2C thin film based on the thermo‐optic effect. A total of 34.67˚ of polarization rotation is achieved with the variation of pump power from 0 to 223 mW. From the regression analysis, the system is operated in highly linear condition, with R 2 value of 0.991 and an efficiency of 0.1589˚/mW. Throughout the polarization rotational range, the variation of ellipticity is less than 5˚ while the variation of output power is less than 3.5 dB.